1998
DOI: 10.1007/bf02496865
|View full text |Cite
|
Sign up to set email alerts
|

Role of calcium and phosphoinositide cell regulatory system in adaptation of neurons in olfactory cortex section toIn Vitro hypoxia

Abstract: Activities of calcium and phosphoinositide regulatory systems in sections of rat olfactory cortex are analyzed during and after anoxia of different duration. It is shown that shortterm anoxia prevents the disturbances in cell regulatory systems induced by long-term anoxia via moderate but sustained rise in neuronal content of second messengers: Ca -' + and products of phosphoinositide hydrolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The method used for studying the dynamics of Ca-c content in brain tissues was based on microfluorimetry using a chlortetracycline fluorescence probe and a LYuMAM-KF contact microscope; this method has been described in detail elsewhere, for in vivo experiments [5,8], and was modified for in vitro conditions [10]. Microregions of slices (150 Ixm in diameter) were used for measurement of the fluorescence intensity of calcium-chlortetracycline complexes bound to intracellular hydrophobic domains, using an excitation wavelength of 407 nm and an emission wavelength of 522 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method used for studying the dynamics of Ca-c content in brain tissues was based on microfluorimetry using a chlortetracycline fluorescence probe and a LYuMAM-KF contact microscope; this method has been described in detail elsewhere, for in vivo experiments [5,8], and was modified for in vitro conditions [10]. Microregions of slices (150 Ixm in diameter) were used for measurement of the fluorescence intensity of calcium-chlortetracycline complexes bound to intracellular hydrophobic domains, using an excitation wavelength of 407 nm and an emission wavelength of 522 nm.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently demonstrated that anoxia of different durations and anoxic conditioning have similar effects on the activities of these systems in cortex slices from rats [10]. The same system was used to show that anoxia lasting 2 min induces the synthesis and release of neuromediator peptides into the extracellular medium of slices; transfer of the medium to recipient slices increased the resistance of neurons in the recipient slices to anoxia lasting 10 rain, preventing depression of synaptic transmission [3,4].…”
mentioning
confidence: 99%
“…Still, the former phenomenon might play a signalling role for the induction of long-lasting tolerance. There is evidence that the mechanism of rapid preconditioning is associated with increased excitability of neurons [10][11][12], activation of A1 adenosine receptors [13], moderate increase in intracellular free and bound Ca 2+ levels and activation of phosphoinositide hydrolysis [14,15], and activation of protein kinase C [16,17], to mention only some examples of signal-related rapid responses to short-term anoxia. Nevertheless, the data accumulated so far are incomplete and no postulation of any unitary mechanism of rapid anoxic preconditioning can yet be made.…”
Section: Introductionmentioning
confidence: 99%